Jovens trabalhadores: estudo sobre as repercussões do trabalho na trajetória de vida de jovens egressos da Cruz Vermelha Brasileira em parceria com a UFMG - Jaqueline Silvério Alves (2023)
This research brings a proposal that falls within the field of Work and Education, specifically, it aims to understand the repercussions of work on the life trajectory of six young people who have completed their work experience at the Brazilian Red Cross Institution of Minas Gerais (CVB-MG ) in partnership with the Federal University of Minas Gerais (UFMG). From the dialogue with authors from the sociology of youth, work and sociology of education, in the theoretical-methodological path, singular experiences and how the individual attributed meaning to their trajectory were highlighted. Research with narratives was also a representative pillar, above all, for valuing the report as a means of investigation and as a form of knowledge production. Through this study, we sought a greater understanding of the relationship between youth, work and education, also thinking about the possible meanings of work within a university. The research problem aims to answer the following question - What is the impact of work experience at CVB-MG/UFMG on the life trajectory of young people? Data were collected through narrative interviews, based on a brief guiding script and recorded using a digital audio recorder, which were transcribed in full and analyzed at a later time. Among the study's notes, we highlighted that the “Youth” category is diverse, as are the subjects that make up it. It brings elements that allow us to reflect on the place that work occupies in the education of poor young people. Based on the information obtained and through the interpretation of the narratives, it is credible to state that, based on the relationships that young people established in this work experience, they had access to different references and a range of information that made it possible to construct multiple ways of seeing and living everyday life. . Although it can be understood as a training process beyond education centers, however, in the work environment, the possibility of enriching experiences and developing the youth condition was not fully presented to everyone, which may have had repercussions on different life trajectories of these young people.